2018
DOI: 10.1007/s00441-018-2872-4
|View full text |Cite
|
Sign up to set email alerts
|

A novel mechanism of autophagy-associated cell death of vasopressin neurons in familial neurohypophysial diabetes insipidus

Abstract: Familial neurohypophysial diabetes insipidus (FNDI), characterized by delayed-onset progressive polyuria and loss of arginine vasopressin (AVP) neuron, is an autosomal dominant disorder caused by AVP gene mutations. We previously generated a knock-in mouse model for FNDI, which recapitulated the phenotype of human FNDI. To address the mechanisms underlying AVP neuron loss, we subjected FNDI mice to intermittent water deprivation, which accelerated the phenotype and induced AVP neuron loss within a relative sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…The late onset of the disease in family 12 may be explained by the fact that this new mutation causes a switch among neutral amino acids, which potentially does not severely affect the biochemical features of the mature protein. The hypothesized mechanisms underlying the phenotype of the two novel mutations could be explained by one of those extensively investigated in the cell lines of patients with adNDI (8,16,17,33). Mutant AVP precursors reportedly accumulate and aggregate in the ER, which leads to defective intracellular trafficking of wild-type AVP protein and a decrease in cell viability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The late onset of the disease in family 12 may be explained by the fact that this new mutation causes a switch among neutral amino acids, which potentially does not severely affect the biochemical features of the mature protein. The hypothesized mechanisms underlying the phenotype of the two novel mutations could be explained by one of those extensively investigated in the cell lines of patients with adNDI (8,16,17,33). Mutant AVP precursors reportedly accumulate and aggregate in the ER, which leads to defective intracellular trafficking of wild-type AVP protein and a decrease in cell viability.…”
Section: Discussionmentioning
confidence: 99%
“…Mutant AVP precursors reportedly accumulate and aggregate in the ER, which leads to defective intracellular trafficking of wild-type AVP protein and a decrease in cell viability. Furthermore, autophagy has been suggested to have a bifunctional role in cell survival and death in a transfected cell lineexpressing mutant NPII (40,41) resulting in autophagy-associated cell death of AVP neurons in mice with familial NDI mice (33). In autosomal dominant CDI, clinical disease onset can be expressed during the neonatal period (8,10), but typically polyuria and polydipsia in adNDI occur during the first months to years of life and progress as AVP deficiency becomes increasingly severe (8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The other part of the mutants is eliminated via ER-associated degradation (ERAD) by proteasomes after retro-translocation to the cytosol [59]. Hagiwara et al recently showed that autophagy should be primarily a protective mechanism, but continuous autophagy leads to a gradual loss of organelles, including the ER, resulting in autophagy-associated cell death of AVP neurons in mice with FNDI [60]. Although the possible loss of vasopressinergic neurons is associated with autophagy, the mechanism leading to cell degeneration in autosomal dominant FNDI is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that macroautophagy or cell death was not observed as long as mutant NPII was confined to the ERACs in FNDI mice with free access to water (Hagiwara et al, 2014). Conversely, ERAC ll OPEN ACCESS iScience Article formation was disrupted and mutant NPII aggregates were spread throughout the ER lumen after intermittent water deprivation, leading to autophagy-associated cell death of AVP neurons in FNDI mice (Hagiwara et al, 2014(Hagiwara et al, , 2019. Taken together, it seems that ERAC formation as well as degradation of mutant proteins within ERACs is essential for protecting AVP neurons from cell death in FNDI.…”
Section: The Accumulation Of Aggregates Within Eracs Is Reduced By Thmentioning
confidence: 99%